Pelatihan Pembuatan Media Pembelajaran STEAM Bagi Guru PPT Wijaya Kusuma RW 04, Kelurahan Banjar Sugihan, Kecamatan Tandes, Kota Surabaya - Mochammad Reizza Al Ariyah; Nabillah Auliya Nur Agrianti; Benita Syifa Calista; Miftahurrohmah Miftahurrohmah; Fidya Almira Naila Yusuf; Shafira Putri Yufa; Diyah Smara Annetta Marjono; Samiaji Dwi Saputra; Lenni Ayu Lestari; Hendrik Kondanamu (Fakultas Teknik Universitas Cenderawasih, 2023)
STEAM (Science, Technology, Engineering, and Mathematics) improvements in education, as well as PAUD teacher inability to effectively use the resources at their disposal despite their simplicity in the classroom. Using active and creative learning approaches, the implementation of learning in STEAM-based PAUD is designed to encourage children's creativity. The method's activities included a pre-test to gauge PAUD teachers' familiarity with the STEAM learning approach, instruction about STEAM resources after that, and training or group practice in creating STEAM-based learning resources. introducing new information, since PAUD teachers did not previously comprehend what STEAM was, They understand now it, and because it combines the five knowledges with basic tools and materials, they can develop it for use as an engaging method of instruction in the future.